Pembuatan Pestisida Nabati Dari Daun Gamal, Daun Tembakau Dan Daun Sirsak Untuk Mengendalikan Hama Ulat Pada Tanaman Pisang - Sri Ngapiyatun (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2017)
This research was conducted in Production Laboratory of Samarinda State Polytechnic of Agriculture. The research took 1 month for tool and material preparations, pesticide production, pesticide application, and data retrieval. There were three treatments i.e. P0 (without vegetable pesticide), P1 (vegetable pesticide made from the mixture of gamal leaf and tobacco leaf), and P2 (vegetable pesticide made out of soursop leaf. Each treatment was repeated five times. In the treatment, the leaves were soaked in the pesticide according to the prescription, the pesticide was then sprayed to the worm-infected-leaves in the jars before the jars were covered for seven days. This research aimed to know the how far the pesticide was effective in controlling the worm on banana leaves by observing the daily activity of the worm. Results show that P1 was the most effective pesticide since on day two after the application, it was visible that some worms have died.